Innovative preclinical drug screening with Data Acquisition Systems Workshop / Assoc. Prof. Dr .Hanish Singh Jayasingh Chellammal and Dr. Gurmeet Kaur Surindar Singh - Jayasingh Chellammal, Hanish Singh; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
Faculty of Pharmacy, UiTM Puncak Alam, has successfully organised a two-day workshop on "Innovative preclinical drug screening with Data Acquisition systems PowerLab" on June 21st-22nd, 2023. This workshop was designed to impart skills in drug discovery and development through pharmacological and toxicological evaluations. The participants of this workshop were external and internal trainees for the PowerLab system. This comprehensive two-day programme organised by the Department of Pharmacology and Pharmaceutical Chemistry, Faculty of Pharmacy, and the CPD committee of the Faculty of Pharmacy, UiTM, involved a series of informative lectures and hands-on sessions, which were conducted in collaboration with Labquip Sdn. Bhd. and AD Instruments, Lexington Drive, Bella Vista, New South Wales, Australia.